Mesenchymal stem cell responses to mechanical stimuli - Delaine-Smith, Robin M. (CIC Edizioni Internazionali, 2012)
Mesenchymal stem cells (MSCs) have the potential to replace or restore the function of damaged tissues and offer much promise in the successful application of tissue engineering and regenerative medicine strategies. Optimising culture conditions for the pre-differentiation of MSCs is a key goal for the research community, and this has included a number of different approaches, one of which is the use of mechanical stimuli. Mesenchymal tissues are subjected to mechanical stimuli in vivo and terminally differentiated cells from the mesenchymal lineage respond to mechanical stimulation in vivo and in vitro. MSCs have also been shown to be highly mechanosensitive and this may present an ideal method for controlling MSC differentiation. Here we present an overview of the response of MSCs to various mechanical stimuli, focusing on their differentiation towards the mesenchymal tissue lineages including bone, cartilage, tendon/ligament, muscle and adipose tissue. More research is needed to elucidate the complex interactions between biochemically and mechanically stimulated differentiation pathways.